1992
DOI: 10.1084/jem.176.6.1645
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of MRL-lpr mice: relationship of the Fas apoptosis gene to disease manifestations and renal disease-modifying loci.

Abstract: SummaryIn MILL mice, the mostly recessive lpr mutation results in both the accumulation of CD4-, identified differences in ILNA expression and differences in the genomic organization of the Fas gene between normal and lpr mice, and confirm the recent report that a mutation in the Fas apoptosis gene is the Ipr mutation. However, our results also indicate that the Fas gene is expressed in spleen cells from normal mice, and spleen and lymph node ceils from mice with a second mutation at the Ipr locus (Ipr% Togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
192
2
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(203 citation statements)
references
References 54 publications
6
192
2
2
Order By: Relevance
“…Previous linkage analyses using autoimmune (NZB, MRL and BXSB) and non-autoimmune strains (NZW, C57BL and B10) did not test the combination of OPN allotypes as in the present study (MRL vs. C3H) [2,3,5] except of a few studies [4,6,17]. In the study of BXSB Â B10 crosses [4,17], to detect the loci with additive mode of inheritance in disease susceptibility might be difficult since authors used BXSB Â (B10 Â BXSB)F 1 or B10 Â (BXSB Â B10)F1 backcrosses, not F 2 crosses.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous linkage analyses using autoimmune (NZB, MRL and BXSB) and non-autoimmune strains (NZW, C57BL and B10) did not test the combination of OPN allotypes as in the present study (MRL vs. C3H) [2,3,5] except of a few studies [4,6,17]. In the study of BXSB Â B10 crosses [4,17], to detect the loci with additive mode of inheritance in disease susceptibility might be difficult since authors used BXSB Â (B10 Â BXSB)F 1 or B10 Â (BXSB Â B10)F1 backcrosses, not F 2 crosses.…”
Section: Discussionmentioning
confidence: 57%
“…In the initial step of this study, three loci were found to be associated significantly with GN, and one of them, Agnm3, turned out to be a novel locus that did not share a chromosomal region with any lupus susceptibility loci reported previously [2][3][4][5][6]8], although some phenotypic loci referring to immune traits were reported such as Lprm4 (lymphoproliferation modifier 4, 54 cM) that was designated by spleen weight in MCN 2 mice [12] and Tsz1 (Thymus size 1, 56 cM) that was designated by thymus size [13]. It should be noted that another study using progenies from B6/lpr and MRL/lpr mice did not show any linkage of GN to Agnm3, even though we employed the same conditions for mouse breeding and histopathologic GN grading as in this study (Zhang et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, other lpr congenic strains of mice that possess the lpr mutation develop lymphoproliferation but not always the lupus disease, depending on their genetic background [44]. At least two additional susceptibility loci in the MRL background have been mapped that are associated with nephritis [45]. We show here that anti-DNA responses followed by a lupus-like disease can be induced in the susceptible MRL/+ mouse strain independent of the Fas defect, and without the associated lymphoproliferation.…”
Section: Discussionmentioning
confidence: 79%
“…The cause of the disease is likely to be multi-factorial, including a single mutation (lpr) of the fas gene and background susceptible genes from the MRL strain [36,37]. The lpr (fas) mutation is believed to be the cause of the lymphoproliferative disorder that interferes with thymic lymphocyte development and differentiation, but its effect on Treg is unclear.…”
Section: Introductionmentioning
confidence: 99%